Influence of Graphite Nodules on the Microstructure and Mechanical Properties of Hollow Ductile Iron Pipe after Austempering Treatment. Issue 12 (7th October 2019) - Wang, Xiaolong; Du, Yuzhou; Gao, Xiangqian; Ge, Yanfeng; Jiang, Bailing
Abstract : Herein, the microstructure and mechanical properties of ductile iron with different numbers of graphite nodules before and after austempering treatment are systematically investigated. The results show that the amounts of graphite nodules affect the microstructure and resulting mechanical properties of ductile iron. The ferrite fraction in an as‐cast matrix decreases with the increase in graphite nodules; this outcome is mainly attributed to the cooling rate. The matrix of ductile iron after austempering treatment is composed of acicular ferrite and retained austenite. The acicular ferrite is refined with the increase in graphite nodules, because the increase in interface between graphite/austenite provides more nucleation sites during austempering treatment. Meanwhile, the formation of ferrite causes carbon atoms to diffuse into the surrounding matrix, giving rise to the increase in carbon concentration of untransformed austenite and further stabilizing the retained austenite. Hence, the volume fraction of retained austenite and the carbon content in it both increase with the increase in graphite nodules. The amounts in graphite nodules affect the mechanical properties significantly after austempering treatment; this outcome is related to the phase constituents of ductile iron after austempering treatment. Herein, the detailed mechanisms are discussed. Abstract : Herein, the influence of graphite nodule counts on the microstructure and mechanical properties of austempered ductile iron is investigated. Obvious differences in the microstructure are observed for samples with different numbers of graphite nodules. The mechanical properties, strength, and ductility are influenced by matrix constituents and graphite nodules.